Biomechanical effects of corticotomy facilitated orthodontic anterior retraction: a 3-dimensional finite element analysis. Issue 7 (18th May 2020) - Liu, Yang; Wu, Yan; Yang, Chongshi; Song, Jinlin; Fan, Yubo
Abstract: The objective of this study was to assess the biomechanical effects of different corticotomy designs used for orthodontic anterior retraction through finite element analysis. Materials and methods: A basic finite element model simulating retraction of anterior teeth was built reversely from CBCT films of an adult patient with protruded maxillary anterior teeth. Another thirteen FE models were created according to different corticotomy designs varied with site width and the extent of incision. The initial displacement, Von Mises stress and pressure stress of dento-alveolar structures was computerized and analyzed. Results: Corticotomy can increase the initial displacement of anterior segment including teeth and surrounding alveolar bone, change the distribution of Von Mises stress in cancellous bone and the pressure stress in periodontal ligament of anterior teeth. When the incision was near the periphery of apical, the anterior segment showed the greatest displacement, the cancellous bone at either sockets or incision region showed the maximum stress. Bilateral incision combined with palatal incision showed approximate initial displacement and stress distribution with circumscribing incision. While the incision width increased, the biomechanical effects of corticotomy amplified. Conclusions: Varied corticotomy designs can change the biomechanical effects on dento-alveolar structures. The incision near the periphery of apical and bilateral incision combined with palatal incision may be the optimized design used for retraction of anterior teeth.